2018
DOI: 10.3390/ijerph15020245
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Retailers to Refuse to Sell Tobacco Products to Minors

Abstract: Tobacco smoking and exposure to secondhand smoke are major environmental risk factors that negatively influence health. It is recommended that tobacco product manufacturers and retailers receive empowerment counseling programs to achieve adolescent health targets. The present study conducted an empowerment counseling session to counsel tobacco product retailers in refusing to sell tobacco products to minors. The three stages of this study were conducted from March 2015 to February 2017. The results revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Furthermore, in the realm of law enforcement, the health tax can also be leveraged to impose more stringent penalties, enhance monitoring efforts, and provide counselling for sellers found illegally selling tobacco and alcohol to minors. (90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the realm of law enforcement, the health tax can also be leveraged to impose more stringent penalties, enhance monitoring efforts, and provide counselling for sellers found illegally selling tobacco and alcohol to minors. (90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the relevant government agencies and other stakeholders must carry out public sensitization and educational campaigns about the tobacco control laws in Nigeria. If these educational programs are effectively executed, they will positively influence vendors' compliance with the laws as it had been successfully used in other countries [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the competent authorities could prevent retailers from selling tobacco products to adolescents in the future by enhancing regular inspections of stores with lower compliance, conducting amendments, and enhancing education training for staff as well as internal norms in tobacco-selling places [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%